FEAR AND ANXIETY EXPERIENCED BY THE CHARACTERS OF A DAVID FINCHER’S FILM TITLED PANIC ROOM - ARIFIN, MUHAMMAD FAHRUL ROSI (Jurnal Ilmiah Mahasiswa FIB, 2015)
Keywords: Freud, real fear, neurotic fear, realistic anxiety, moral anxiety, neuroticanxiety, object.Humans are the most wonderful creatures who have ability to think much better than other creatures. They all have their own mindset that differentiates one and another. The illustration of various humans’ personality can be seen from film. It usually tells story about human’s life and behavior that can be analyzed. Panic Room, a thriller film by David Fincher involves a family which is threatened by unfamiliar people or strangers, in this case are the thieves. This study applies psychoanalysis as theory, because it explains about humans’ nature behavior. There are a lot of concerns in connection with psychoanalysis including fear and anxiety.Freud explains that there are two kinds of fear: neurotic fear and real fear; and three kinds of anxiety: neurotic, realistic, and moral anxiety. Even though fear and anxiety seem similar but they are actually different. In Panic Room, there are some events that indicate fear and anxiety. It also shows the reaction from the characters when they experience fear or anxiety. The reactions to fear shown by the characters are flight, defense, and attack. However, anxiety is usually followed by physical sensations, such as trembling or crying.The result of this study shows that even though the characters show that their fears are caused by the same object although they may show different reaction to it. The different reaction shown by the characters is influenced by the past experiences they have had earlier. The characters that experienced anxiety show different causes and reaction to their anxiety. The writer suggests the next researcher to analyze defense mechanism shown in Panic Room Film because it has close connection which anxiety studied in this thesis.